Consecutive-Day Ventricular and Atrial Cardiomyocyte Isolations from the Same Heart: Shifting the Cost–Benefit Balance of Cardiac Primary Cell Research - Joachim Greiner; Teresa Schiatti; Wenzel Kaltenbacher; Marica Dente; Alina Semenjakin; Thomas Kok; Dominik J. Fiegle; Thomas Seidel; Ursula Ravens; Peter Kohl; Rémi Peyronnet; Eva A. Rog-Zielinska (Cells, 2022)
Freshly isolated primary cardiomyocytes (CM) are indispensable for cardiac research. Experimental CM research is generally incompatible with life of the donor animal, while human heart samples are usually small and scarce. CM isolation from animal hearts, traditionally performed by coronary artery perfusion of enzymes, liberates millions of cells from the heart. However, due to progressive cell remodeling following isolation, freshly isolated primary CM need to be used within 4–8 h post-isolation for most functional assays, meaning that the majority of cells is essentially wasted. In addition, coronary perfusion-based isolation cannot easily be applied to human tissue biopsies, and it does not straightforwardly allow for assessment of regional differences in CM function within the same heart. Here, we provide a method of multi-day CM isolation from one animal heart, yielding calcium-tolerant ventricular and atrial CM. This is based on cell isolation from cardiac tissue slices following repeated (usually overnight) storage of the tissue under conditions that prolong CM viability beyond the day of organ excision by two additional days. The maintenance of cells in their near-native microenvironment slows the otherwise rapid structural and functional decline seen in isolated CM during attempts for prolonged storage or culture. Multi-day slice-based CM isolation increases the amount of useful information gained per animal heart, improving reproducibility and reducing the number of experimental animals required in basic cardiac research. It also opens the doors to novel experimental designs, including exploring same-heart regional differences.